Physical and Mechanical Properties Assessment for Particle Board made from Sugarcane Fiber - Boupha, thavongsuk (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aimed to assess the water absorption, thickness swelling, density, shrinkage, Modulus of Elasticity (MOE), Modulus of Rupture (MOR), and sound insulation properties of particle board made from sugarcane fiber. Sugarcane fibers were cut into lengths of 0.3–0.5 cm and dried in a solar kiln to achieve a moisture content between 5% and 10%. A mixture of 1500 g of sugarcane fiber, 166 g of citric acid, and 283 g of water was prepared and pressed into a metal frame measuring 27 × 400 × 400 mm at a temperature of 200°C for 30 minutes. The resulting particle board sheets were then cut into sizes specified by the standard test methods. The results showed that the particle board had a water absorption rate of 143.8%, thickness swelling of 19.0%, density of 353.82 kg/m³, thickness shrinkage of 1.69%, and longitudinal shrinkage of 0.8%. The MOE was 68.6 N/mm² for the board without surface paper, and 83.0 N/mm² for the board with top and bottom surface paper. The MOR was 0.65 N/mm² without surface paper and 1.0 N/mm² with surface paper. Additionally, the particle board demonstrated a 45% reduction in sound transmission, indicating its potential for sound insulation applications.